PENERAPAN MODEL PEMBALAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 011 PONDOK GELUGUR KECAMATAN LUBUK BATU JAYA KABUPATEN INDRAGIRI HULU. - Idris, Junaidi; Witri, Gustimal; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstraction: The problem in this research is the low teacher motivation to the students in learning. The teacher did not use the knowledge that were had by the students for giving study experience, the teacher did not ask the student to review the materials which were given in the class, so the information that they got did not observed maximally in students mind and quickly disappear. That problem will influence students’ achievement. Based on that problem, it is necessary to find the way to solve the problem. One of them is The Implementation of Quantum Teaching Model to increase students’ achievement. Through The Implementation of Quantum Teaching Model will create please and enjoyable study atmosphere for the students. The subject of this research is the students of Public Elementary School 011 Pondok Gelugur in 2014/2015 with 16 students become a data sources. This research was conducted in two phases, each phase consist of four steps. They are planning, implementation, observation and reflection. The instrument collecting data in this thesis is a test to measure the science achievement, observation project to measure study activities. Data analysis technique which was used data analysis quantitative and qualitative. This research is the Classroom Action Research (PTK), which was conducted to increase study achievement of science lesson of students’ of Public Elementary School 011 Pondok Gelugur Lubuk Batu Jaya Sub District with The Implementation of Quantum Teaching Model. The result of this research showed that The Implementation Quantum Teaching Model can increase students’ achievement in studying science lesson. It can be proven by (1) there is enhancement on class average score which are in pretest is 66,6, first phase is 68,9 and in second phase increase to 81,9. From the average score which is gained, there is enhancement in study achievement is 5,18% in first phase and 29,31% in second phase; (2) minimum criteria passing grade classically (KKM 70) in pretest 50% first phase test 62,5%, after conducting the reflection in 6 students who did not pass KKM ( below 70), and in second phase became 97,75%, after reflection overall, the enhancement had increased if we saw from the percentage of the completeness of the students; (3) in student learning activities also showed enhancement. In first phase the percentage of learning activities of the students is 75,0% whereas in second phase reached 87,5% so the enhancement student learning activities is 12,5%. Whereas in teaching activities of the teacher increase in first phase is 78,8% and in second phase increase to 88,8% so the enhancement that teacher did is 10%.Keywords : Quantum Teaching Model, Study Achievement